Capacity of Nine Thermostable DNA Polymerases To Mediate DNA Amplification in the Presence of PCR-Inhibiting Samples - Abu Al-Soud, Waleed (American Society for Microbiology, 1998)
The PCR is an extremely powerful method for detecting microorganisms. However, its full potential as a rapid detection method is limited by the inhibition of the thermostable DNA polymerase from Thermus aquaticus by many components found in complex biological samples. In this study, we have compared the effects of known PCR-inhibiting samples on nine thermostable DNA polymerases. Samples of blood, cheese, feces, and meat, as well as various ions, were added to PCR mixtures containing various thermostable DNA polymerases. The nucleic acid amplification capacity of the nine polymerases, under buffer conditions recommended by the manufacturers, was evaluated by using a PCR-based detection method for Listeria monocytogenes in the presence of purified template DNA and different concentrations of PCR inhibitors. The AmpliTaq Gold and the Taq DNA polymerases from Thermus aquaticus were totally inhibited in the presence of 0.004% (vol/vol) blood in the PCR mixture, while the HotTub, Pwo, rTth, and Tfl DNA polymerases were able to amplify DNA in the presence of 20% (vol/vol) blood without reduced amplification sensitivity. The DNA polymerase from Thermotoga maritima (Ultma) was found to be the most susceptible to PCR inhibitors present in cheese, feces, and meat samples. When the inhibitory effect of K and Na ions was tested on the nine polymerases, HotTub from Thermus flavus and rTth from Thermus thermophilus were the most resistant. Thus, the PCR-inhibiting effect of various components in biological samples can, to some extent, be eliminated by the use of the appropriate thermostable DNA polymerase.